Artificial intelligence and workers' well-being - Osea Giuntella; Johannes König; Luca Stella (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This study explores the relationship between artificial intelligence (AI) and workers' well-being and mental health using longitudinal survey data from Germany (2000-2020). We construct a measure of individual exposure to AI technology based on the occupation in which workers in our sample were first employed and explore an event study design and a difference-in-differences approach to compare AI-exposed and non-exposed workers. Before AI became widely available, there is no evidence of differential pre-trends in workers' well-being and concerns about their economic futures. Since 2015, however, with the increasing adoption of AI in firms across Germany, we find that AI-exposed workers have become less satisfied with their life and job and more concerned about job security and their personal economic situation. However, we find no evidence of a significant impact of AI on workers' mental health, anxiety, or depression.
Keywords: I10; J28; O30; 330; Artificial Intelligence; Future of Work; Well-being; Mental Health